Empowering the connected physician in the e-patient era : how physician's empowerment on digital health tools can improve patient empowerment and boost health(care) outcomes /: how physician's empowerment on digital health tools can improve patient empowerment and boost health(care) outcomes. (2018) - Affinito, Letizia
No abstract available